Substrates of Mauritia flexuosa and wastewater from pig farming on growth and quality in seedlings of Acacia mangium - Araújo, Emanuel; Arauco, Adriana; Dias, Bruna Anair; Silva, Gustavo; Nóbrega, Rafaela (Revista Ciência Agronômica, 2018)
Sustainable alternatives should be adopted to minimise the negative environmental impacts of agricultural activities. The use of wastewater as well as organic waste, from agricultural activities or found naturally, such as the decomposed stems of the Buriti palm (Mauritia flexuosa), can be a sustainable alternative in the production of seedlings for the reforestation of areas in the process of degradation or desertification, common in the State of Piauí, Brazil. The aim of this study was to evaluate growth and quality in seedlings of Acacia mangium Willd grown in substrates with different proportions of decomposed stems of Mauritia flexuosa (DSB), and irrigated with wastewater from pig farming (WPF). The experimental design was completely randomised, arranged in a 5 x 2 factorial scheme, corresponding to five proportions of DSB and soil (v/v,% - 0:100, 20:80, 40:60, 60:40, 80:20), and two sources of irrigation water (well water and WPF), with four replications. At 100 days after sowing (DAS), the seedlings were collected to measure the variables related to growth, quality and nodulation. Height, root collar diameter, shoot dry weight, leaf area and nitrogen accumulation in the shoots were significantly influenced (p≤0.05) by the interaction between substrate and source of irrigation water. The WPF had no significant influence on the growth or quality of the Acacia mangium Willd seedlings. The best ratio between DSB substrate and soil was 46:54, considered the most suitable for seedling production in Acacia mangium Willd.